Digital Image Processing Education for Detection and Knowledge Information Hidden in Images - Negoro, Wahyu Sapta; Azhar, Asbon Hendra; Destari, Ratih Adinda; Syahrian, Achmad (Jurnal TUNAS, 2024)
AbstractDigital Image Processing, known as Digital Image Processing, is a scientific discipline related to techniques for processing an image using a computer. There are several types of images, namely color images (RGB), grayscale images (grayscale), binary images (monochrome) (Akhmad Fadjeri et al, 2023). In the world of medicine, image segmentation is used to detect an object in a medical image or analyze the nature of a disease such as eye disease (keratitis) (Kon et al, 2023).Image is a representation or can also be said to be a picture, imitation, imitation, or similarity, of a particular object. Images, when grouped based on the type of data that makes up the image, are divided into 2 types, namely analog images and digital images (Yao et al, 2022). Analog Images and Digital Images Analog images are produced using analog tools, such as analog video cameras, CT scans, analog photo cameras, x-ray sensors for thorax photos, cams, short wave sensors in radar systems, ultrasound sensors in ultrasound systems, and others. -other (Tarpley et al., 2021).